Eksplorasi Disposisi Berpikir Kritis Siswa SMP Negeri 2 Balai - Adhitya Rahardhian; Indri Astuti; A Afandi (Universitas Sarjanawiyata Tamansiswa, 2022)
Education is not only a transfer of knowledge but also useful for developing 21st-century skills. One of the 21st-century skills is critical thinking. Critical thinking disposition is a requirement to be able to master critical thinking skills. The purpose of this study was to explore the critical thinking disposition of students SMP Negeri 2 Balai. This research is quantitative descriptive research using the survey method. Research respondents totaled 243 students. The instrument used was adapted from the Student-Educator Negotiated Critical Thinking Dispositions Scale (SENCTDS). SENCTDS consists of 21 questions in the form of a Likert scale with 5 choices of response scales. From the research, it is known that students have a high category disposition on reflection (3,48), organisation (3,60), perseverance (3,63), and intrinsic goal motivation (3,53). Low category disposition on attentiveness (2,85) and open-mindedness (2,67). The study revealed that students' critical thinking dispositions decreased with the increase in grades.